Pengaruh pendidikan kesehatan tentang penyakit leptospirosis dengan metode ceramah kesehatan terhadap tingkat pengetahuan dan sikap warga di desa bakaran kulon juwana kabupaten pati - Satriyo W, Arif; , Tri Puji Kurniawan, SKM, M. Kes; , Anisa Catur Wijayanti, SKM., M.Epid (2014)
Leptospirosis represents the disease zoonosis which is because of bacterium infection which is in form of spiral from gender leptospira which patogen, and most contagious dominant by water of mouse urine. Pursuant to antecedent survey in Burnup Kulon Village, from 20 people 16 among others don't know the disease leptospirosis supported with the indisposed condition sanitasi house. Health education with speech method done utilize to grow the caring to program of prevention and contagious disease leptospirosis operation by mouse urine. Purpose of this research is to know the picture and the influence of health education about leptospirosis disease with health speech method to knowledge level and attitude citizen in Bakaran Vilage Kulon Juwana of Pati Regency. This research method use the Quasi Experiment by pre-test and post-test control group and sampel counted 94 family head in Burnup Kulon Village taken with proportional random sampling technique. The data analyse technique use Wilcoxon Signed Rank, Paired T test and Mann Whitney U Test. Result of analysis known the majority of control group to old age 31-40 year ( 33%) and 51-60 year ( 34%) for experiment group, work as farmer / labour at the both group, control group ( 64,9%) and experiment group (68,1%) and also have elementary school education for the both group, control group (64,9%) and experiment group ( 63,8%). Knowledge level of experiment group when pre-test is enough (64,9%) and after post-test become the goodness ( 66%). While knowledge level control group when pre-test is less (45,7%) and after post-test become enough (44,7%). Attitude the experiment group is unfavourable when pre-test (71,3%) and after post-test become the goodness (95,7%). While at control group when pre-test is unfavourable attitude (74,5%) and after post-test remain to behave unfavourable (68,1%). So can conslusion that there is influence of health education about leptospirosis disease with health speech method to knowledge level and attitude citizen in Bakaran Vilage Kulon Juwana of Pati Regency ( p value = 0,000 < 0,05).